![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
x(x-5).(x+5)-(x+2).(x^2-2x+4)=17
\(\Leftrightarrow x\left(x^2-25\right)-\left(x^3-2x^2+4x+2x^2-4x+8\right)=17\)
\(\Leftrightarrow x^3-25x-x^3+2x^2-4x-2x^2+4x-8=17\)
\(\Leftrightarrow-25x=17+8\)
\(\Leftrightarrow-25x=25\)
\(\Leftrightarrow x=-1\)
#)Giải :
\(x\left(x-5\right)\left(x+5\right)-\left(x+2\right)\left(x^2-2x+4\right)=17\)
\(\Rightarrow x\left(x^2-25\right)-\left(x^3-2x^2+4x+2x^2-4x+8\right)=17\)
\(\Rightarrow x^3-25-\left(x^3+8\right)=17\)
\(\Rightarrow x^3-25x-x^3-8=17\)
\(\Rightarrow-25x=25\Rightarrow x=-1\)
Vậy x = -1
![](https://rs.olm.vn/images/avt/0.png?1311)
x(x - 5)(x + 5) - (x + 2)(x2 - 2x + 4) = 17
=> x(x2 - 25) - (x3 + 23) = 17
=> x3 - 25x - x3 - 8 = 17
=> 25x - 8 = 17
=> 25x = 17 + 8
=> 25x = 25
=> x = 1
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\left(x+2\right)^2=4\left(2x-1\right)^2\)
\(\left(x+2\right)^2-4\left(2x-1\right)^2=0\)
\(\left(x+2\right)^2-\left[2\left(2x-1\right)\right]^2=0\)
\(\left(x+2\right)^2-\left(4x-2\right)^2=0\)
\(\left(x+2-4x+2\right)\left(x+2+4x-2\right)=0\)
\(6x\left(-3x+4\right)=0\)
\(\Rightarrow6x=0\) hoặc \(-3x+4=0\)
*) \(6x=0\)
\(x=0\)
*) \(-3x+4=0\)
\(3x=4\)
\(x=\dfrac{4}{3}\)
Vậy \(x=0;x=\dfrac{4}{3}\)
b) \(4x\left(x-2019\right)-x+2019=0\)
\(4x\left(x-2019\right)-\left(x-2019\right)=0\)
\(\left(x-2019\right)\left(4x-1\right)=0\)
\(\Rightarrow x-2019=0\) hoặc \(4x-1=0\)
*) \(x-2019=0\)
\(x=2019\)
*) \(4x-1=0\)
\(4x=1\)
\(x=\dfrac{1}{4}\)
Vậy \(x=\dfrac{1}{4};x=2019\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(x^2+1\right)\left(x-2\right)+2x=4\Leftrightarrow x^3-2x^2+x-2+2x-4=0\Leftrightarrow x^3-2x^2+3x-6=0\Leftrightarrow\left(x-2\right)\left(x^2+3\right)=0\Leftrightarrow x-2=0\Leftrightarrow x=2\)(do \(x^2+3\ge3>0\))
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{3x+2}{x-1}+\frac{2x-4}{x+2}=5\)
<=> \(\frac{3x+2}{x-1}+\frac{2\left(x-2\right)}{x+2}=5\)
<=> (3x + 2)(x + 2) + 2(x - 2)(x - 1) = 5(x - 1)(x + 2)
<=> 3x2 + 6x + 2x + 4 + 2x2 - 2x - 4x + 4 = 5x2 + 10x - 5x - 10
<=> 5x2 + 2x + 8 = 5x2 + 5x - 10
<=> 5x2 + 2x + 8 - 5x2 = 5x - 10
<=> 2x + 8 = 5x - 10
<=> 2x + 8 - 5x = -10
<=> -3x + 8 = -10
<=> -3x = -10 - 8
<=> -3x = -18
<=> x = 6
![](https://rs.olm.vn/images/avt/0.png?1311)
Sửa đề: \(\left(x-2\right)^3-\left(x+2\right)\left(x^2-2x+4\right)+\left(2x-3\right)\left(3x-2\right)=0\)
\(\Leftrightarrow x^3-6x^2+12x-8-x^3-8+6x^2-13x+6=0\)
=>-x-10=0
=>x=-10
![](https://rs.olm.vn/images/avt/0.png?1311)
PT <=> \(\left(2x+5\right)\left(x-4\right)-\left(x-4\right)\left(5-x\right)=0\)
<=> \(\left(x-4\right)\left(2x+5-5+x\right)=0\)
<=> \(\left(x-4\right).3x=0\)
<=> \(\left[{}\begin{matrix}x=4\\x=0\end{matrix}\right.\)
KL: \(S=\left\{4;0\right\}\)